2023
DOI: 10.1002/pol.20230230
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structure–sensitivity relationship of photosensitive polyimide formulated by using a photobase generator

Abstract: Photosensitive polyimides (PSPIs) have been widely used in the buffer coating layer and insulation layer due to their excellent thermal and mechanical stability. In this work, a series of negative‐type PSPIs based on poly(amic acid) (PAA) and a photobase generator (PBG) have been developed. Two diamines of 4,4′‐oxydianiline (ODA), 3,3′‐diaminodiphenyl sulfone (SDA), and four dianhydrides of pyromellitic dianhydride (PMDA), 3,3′,4,4′‐biphenyltetracarboxylic dianhydride (BPDA), 4,4′‐oxydiphthalic anhydride (ODPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…101 For instance, Chang et al found that the high optical transparency and low rigidity of the polyimide backbone give a significant promotion on the performance of PSPI, especially for the photosensitivity, owing to the designed wide optical bandgap and low rigidity are beneficial for the photochemical reaction and chemical imidization. 102 In 2019, Noda et al fabricated nega-type patterns efficiently attained by polysilane solution with optimum ratio of OXTA-P2 t Bu (1.8 : 1) as a PBG under UV irradiation, where the ratio determined by the observations on pH change, ESR and UV absorption spectra, combining with quantum chemical calculation. 17 These work re-confirmed the important role of designs on molecular structures, compositions of the PBGs and monomers, even for the design of fluorescent species, no matter these species are derived from organic molecules or nanomaterials, which could become the mainstream method to expand the family of highly efficient PBGs, further promoting their microelectronic applications, particularly in the photoresist aspect in the future.…”
Section: Photobase Generators: Towards High-quality Photoresistsmentioning
confidence: 99%
“…101 For instance, Chang et al found that the high optical transparency and low rigidity of the polyimide backbone give a significant promotion on the performance of PSPI, especially for the photosensitivity, owing to the designed wide optical bandgap and low rigidity are beneficial for the photochemical reaction and chemical imidization. 102 In 2019, Noda et al fabricated nega-type patterns efficiently attained by polysilane solution with optimum ratio of OXTA-P2 t Bu (1.8 : 1) as a PBG under UV irradiation, where the ratio determined by the observations on pH change, ESR and UV absorption spectra, combining with quantum chemical calculation. 17 These work re-confirmed the important role of designs on molecular structures, compositions of the PBGs and monomers, even for the design of fluorescent species, no matter these species are derived from organic molecules or nanomaterials, which could become the mainstream method to expand the family of highly efficient PBGs, further promoting their microelectronic applications, particularly in the photoresist aspect in the future.…”
Section: Photobase Generators: Towards High-quality Photoresistsmentioning
confidence: 99%
“…In this context, low-dielectric materials have attracted much interest. Particularly, polyimide (PI) films are considered as one of the most promising candidates for the next generation of dielectrics due to their excellent thermal [6][7][8], mechanical [9,10], and dielectric properties [11][12][13][14][15], and have been applied in insulation layers, buffer coatings, and passivation layers in the microelectronics industry [16][17][18][19]. However, it is a fact that the dielectric constant of most PI films is not low enough (approximately 3.2-4.0).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Photosensitive polyimide (PSPI) simplifies traditional PI processing. 7,[9][10][11][12][13] The graphic technology of PI has also developed. 14 Fabricating PI pattern becomes more convenient.…”
Section: Introductionmentioning
confidence: 99%